Wilderness Experience in the Promotion of Sustainable Reconciliation - McMullen, Henry G. (Trinity College Dublin, 2007)
This research will examine the role and value of wilderness and nature-based activities for the healing of those traumatised by violence, and in the building of sustainable peace.
Exhibited at the second Glucksman Memorial Symposium on June 13th 2007
Keywords: Wilderness Experience; Glencree Centre for Reconciliation; British-Irish Conflict